(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Ario A, Kartono AP, Prasetyo LB, Supriatna J. 2018. Post-release adaptation of Javan gibbon (Hylobates moloch) in Mount Malabar Protected Forest, West Java, Indonesia. Biodiversitas 19: 1482-1491. Post-release adaptation study of Javan gibbon (Hylobates moloch) was conducted in twelve months from April 2016 to March 2017 in the Mount Malabar Protected Forest, West Java. We studied eleven Javan gibbons released between March 2014 to August 2016. The purpose of this study was to assess the adaptive ability of the released Javan gibbons. Data collection was conducted by focal animal sampling method with 5-minute interval recording time and ad libitum method. The average time allocation of Javan gibbon activities was the following: feeding 23.02±1,62%; moving 26.95±3.07%; resting 40.88±3.81%; socializing 7.56±3.55%; sexual 0.26±0.24%; and vocalizing 0.95±0.21%. We compared activity allocation data from this study and those from wild Javan gibbons and found similarities as follows: 47.60% at a family of Jowo-Bombom-Yani-Yudi, 62.45% at a pair of Moly-Nancy, 51.70% at a pair of Robin-Moni and 52.58% at a family of Mel-Pooh-Asri. Post-release adaptation of Javan gibbon is influenced by internal and external factors. Internal factor includes the ability of each individual to develop wild behavior according to its gender and age group, in terms of natural fruit consumption, brachiation movement, morning calls and alarm calls, as well as affiliative bonds among individuals. External factors include the ability of Javan gibbon to adapt to the environment, namely weather conditions and human presence.